ANALISIS PENGARUH FAKTOR-FAKTOR KOMPETENSI TERHADAP KINERJA KARYAWAN PT TASPEN (PERSERO) KCU SEMARANG - Palokoto, Alifia; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2014)
This research aims to analyze the influences of competence factors to employee performance of PT TASPEN (Persero) Semarang main branch. This research utilize independent variables, they are integrity, achieve orientation, concern for order, customer service orientation, interpersonal understanding combined to a dependent variable of employee performance. This research focuses on five mandatory competence owned by the whole employees of PT TASPEN (Persero) Semarang main branch. The fact that three of them shows a lower percentage. For those reasons, it is needed to know how much the mandatory competence influence owned by the employees performance.Research method used is that quantitative analyze, with validity and reliability tests, classical assumption test, double linear regression analyze collected through questioners spreading and implemented to the whole employees of 85 persons.Based on the done research in the past, it showed that all independent variables had positive and significant influences to the employees performance with the integrity variable influence to the employees performance reached 0,238; the achieve orientation variable influence to the employees performance reached 0,297; the concern for order variable influence to the employees performance reached 0,230; the customer service orientation variable influence to the employees performance reached 0,285; the interpersonal understanding variable influence to the employees performance reached 0,294.